Validity and Reliability of Peristomal Skin Assessment Instruments: Integrative Review - Alimuddin Ali; Syahrul Syahrul; Yuliana Syam; Sintawati Majid; Syaiful Syaiful (Jurnal Keperawatan, 2022)
The incidence of early complications such as skin irritation, erosion, and peristomal ulceration is reported to be quite high. It is important to assess the peristomal skin in order to prevent complications. Valid and reliable instruments are needed to collect assessment data. This integrative review aims to summarize and identify the current literature related to valid and reliable peristomal assessment instruments. An integrative review was carried out using published literature during the search period March 9, 2007-9 March 2022. Database using PubMed, Science Direct, EBSCO, ProQuest, Cochrane Library, and Wiley Online Library. Study selection (both on title/abstract screening and full-text screening) was carried out by two independently experienced reviewers. disagreements were resolved by the decision of the third reviewer. A total of 7 peristomal skin assessment instruments were found from 10 articles passed as the main study. Among the peristomal skin assessment instruments that have good value and process validation and reliability are Ostomi Skin Tools  dan Studio Alterazioni Cutanee Stomali. Peristomal skin assessment as an effort to prevent early stoma complications can be carried out by conducting an assessment using a valid and reliable measuring instrument, and practically easy to introduce.